EVALUASI PENGELOLAANPARIWISATAPADA OBJEK WISATA MUSEUM LAWANG SEWUDI KOTA SEMARANG - Adhinegara, Krisna Yudha; Rahman, Amni Zarkasyi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
The aim of this research is to explain about tourism management evaluation at Lawang Sewu Museum by using Reinesto’s Model and the factors that influence it. This research use descriptive qualitative research that focus on Policy Assessment of the Place of Branding on Lawang Sewu Tourism Objects in Semarang City, and locus in Semarang City. The informants used were the Semarang City Culture and Tourism Office, Travelers, and Community in the City of Semarang. This research used: primary data and secondary data, with data collection techniques: Interview, observation, documentation, and literature. Analysis Techniques that used is dominant analysis through: data reduction, testing data, and drawing verification conclusions. Overall, the place branding at Lawang Sewu Museum is quite good. The Supporting factors are: There are cleaners, and security officers, there are those related to training for tour guides in Semarang, the deft and innovative Lawang Sewu Museum tourism object manager.The Inhibiting factors are: the importance of human resources managing lawang sewu museum; less effective promotions, reduce sales outlets; maintenance of expensive Lawang Sewu tourist buildings, and poor parking. Suggestions were given: increased promotions, approved employees, periodic maintenance, routine training, and consistency and commitment from the manager of Lawang Sewu Museum and Semarang City government attractions.